(untitled) (New York, 1997)
This manual provides instructions and guidelines for using the four texts separately or in various combinations to suit particular program needs. For each of the texts, there is a separate section with answer keys and teaching tips. There is also a midterm and final examination as well as a placement test for use with the entire Interactions program
Keywords: English language,English language; Spoken english - problems, exercises, etc